RANCANG BANGUN APLIKASI PENGELOLAAN POTENSI DESA SEBAGAI SARANA PUBLIKASI MENGGUNAKAN FRAMEWORK CODEIGNITER DI DESA BANYUSARI - Lespi Suryanti (PROCEEDING STIMA)
Potential villages are all natural resources and human resources contained and stored in the village that can be utilized for the sustainability and development of the village. the potential of existing villages in the village of Banyusari large enough both already utilized and which have not been utilized to the fullest. Banyusari village has diverse potentials, but not so well known by the wider community due to lack of information and applications in the potential data collection of the village. The data on the potential of existing villages in Banyusari village is difficult to analyze because there is no special application for the potential management of the village so to get information about the potential in the village takes time to perform a long enough analysis. By looking at these problems, the authors build a potential village management application as a means of publication using the Codeigniter framework. The research methodology used is SDLC (System Development Life Cycle). The end result of the built application system is used to assist in managing the potential of the village, disseminating information about the village and various potentials of the village to the wider community, so as to produce accurate data. With this application system, it is expected that various potential management problems can be solved well and can be useful to help rural development.